Bodily Resurrection in the Quran and the Bible - Enayatollah Sharifi; Mohammad Hossein Khavaninzadeh; Alireza Ansarimanesh (پژوهش نامه معارف قرآنی, 2015)
Resurrection and return of human is innate and natural that has been affecting human life and activities throughout the history. Divine religions have confirmed this belief. But howness of this return is placed under the category of bodily resurrection which has been explained in different ways in the teachings of the three religions. The resurrection in the divine religions of Islam, Christianity and Judaism, is physical. The physical resurrection is explained in the Holy Quran and Bible passages both similarly and differently in different cases. The emphasis on the resurrection of the body and the return of the body from the soil are among the characteristics of bodily resurrection in both Quran and Bible. In this regard, the extent and scope of the teachings of the Quran and the Bible have some differences. Among the differences of the bodily resurrection in the Quran and the Bible are speaking human organs and inanimate objects, animal’s resurrection, resemblance of divine body with earthly body, the fate of human body. There is also a great deal of common ground between the Quran and the Bible.